Mechanisms and time-resolved dynamics for trihydrogen cation (H 3 + ) formation from organic molecules in strong laser fields - Ekanayake, Nagitha; Nairat, Muath; Kaderiya, Balram; Feizollah, Peyman; Jochim, Bethany; Severt, Travis; Berry, Ben; Pandiri, Kanaka Raju; Carnes, Kevin D.; Pathak, Shashank; Rolles, Daniel; Rudenko, Artem; et al. (My University, 2017)
Strong-field laser-matter interactions often lead to exotic chemical reactions. Trihydrogen cation formation from organic molecules is one such case that requires multiple bonds to break and form. We present evidence for the existence of two different reaction pathways for H3 + formation from organic molecules irradiated by a strong-field laser. Assignment of the two pathways was accomplished through analysis of femtosecond time-resolved strong-field ionization and photoion-photoion coincidence measurements carried out on methanol isotopomers, ethylene glycol, and acetone. Ab initio molecular dynamics simulations suggest the formation occurs via two steps: the initial formation of a neutral hydrogen molecule, followed by the abstraction of a proton from the remaining CHOH2+ fragment by the roaming H2 molecule. This reaction has similarities to the H2 + H2 + mechanism leading to formation of H3 + in the universe. These exotic chemical reaction mechanisms, involving roaming H2 molecules, are found to occur in the ~100 fs timescale. Roaming molecule reactions may help to explain unlikely chemical processes, involving dissociation and formation of multiple chemical bonds, occurring under strong laser fields.
Citation: Ekanayake, N., Nairat, M., Kaderiya, B., Feizollah, P., Jochim, B., Severt, T., … Dantus, M. (2017). Mechanisms and time-resolved dynamics for trihydrogen cation (H 3 + ) formation from organic molecules in strong laser fields. Scientific Reports, 7(1), 4703. https://doi.org/10.1038/s41598-017-04666-w
Keywords: Atomic and molecular interactions with photons; Chemical physics; Galaxies and clusters; Reaction kinetics and dynamics